Masonry infilled frame structures: state-of-the-art review of numerical modelling - Tarque, Nicola (2015)
This paper presents a state-of-the-art review of the nonlinear modelling techniques available today for describing the structural behaviour of masonry infills and their interaction with frame structures subjected to in-plane loads. Following brief overviews on the behaviour of masonry-infilled frames and on the results of salient experimental tests, three modelling approaches are discussed in more detail: the micro, the meso and the macro approaches. The first model considers each of the infilled frame elements as separate: brick units, mortar, concrete and steel reinforcement; while the second approach treats the masonry infill as a continuum. The paper focuses on the third approach, which combines frame elements for the beams and columns with one or more equivalent struts for the infill panel. Due to its relative simplicity and computational speed, the macro model technique is more widely used today, though not all proposed models capture the main effects of the frame-infill interaction.